2021
DOI: 10.1038/s41467-021-27140-8
|View full text |Cite
|
Sign up to set email alerts
|

Ezh2 is essential for the generation of functional yolk sac derived erythro-myeloid progenitors

Abstract: Yolk sac (YS) hematopoiesis is critical for the survival of the embryo and a major source of tissue-resident macrophages that persist into adulthood. Yet, the transcriptional and epigenetic regulation of YS hematopoiesis remains poorly characterized. Here we report that the epigenetic regulator Ezh2 is essential for YS hematopoiesis but dispensable for subsequent aorta–gonad–mesonephros (AGM) blood development. Loss of EZH2 activity in hemogenic endothelium (HE) leads to the generation of phenotypically intact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 71 publications
(85 reference statements)
0
2
0
Order By: Relevance
“…Whole‐genome expression arrays in a previous study indicated the involvement of EZH2 target genes in the Wnt signaling pathway [45]. Another study pointed out that nearly half of Wnt signaling genes were EZH2 target genes and that deletion of EZH2 dysregulated Wnt signaling [46]. Thus, we assumed that the Wnt1/β‐catenin signaling pathway was one major component of the regulation of peritoneal angiogenesis by EZH2.…”
Section: Discussionmentioning
confidence: 91%
“…Whole‐genome expression arrays in a previous study indicated the involvement of EZH2 target genes in the Wnt signaling pathway [45]. Another study pointed out that nearly half of Wnt signaling genes were EZH2 target genes and that deletion of EZH2 dysregulated Wnt signaling [46]. Thus, we assumed that the Wnt1/β‐catenin signaling pathway was one major component of the regulation of peritoneal angiogenesis by EZH2.…”
Section: Discussionmentioning
confidence: 91%
“…Similar to metabolic activity, epigenetic regulation of gene expression has also been explored in the transition switches accompanying developmental haematopoiesis and foetal to adult HSC transitions. Several epigenetic regulators have been shown to differentially affect the successive haematopoietic waves, as exemplified by EZH2 [ 133 ], LSD1 [ 134 ] and HDAC1/2 [ 135 ], whose developmental knockouts hinder EMP formation in the yolk sac, but not intra-aortic specification of progenitors and HSC.…”
Section: Pitfalls and Potential Opportunities For Haemogenic Gastrulo...mentioning
confidence: 99%